KNOWLEDGE, ATTITUDES, AND PRACTICES TOWARD HUMAN PAPILLOMAVIRUS (HPV) AND ITS VACCINE - Anni, Naharin Sultana (My University, 2025)
Background Human papillomavirus (HPV) is the most common sexually transmitted infection worldwide, responsible for a rising burden of cancer and disease in both women and men. Despite the proven effectiveness of HPV vaccination, uptake and awareness lag far behind global targets, particularly among men and in low- and middle-income countries (LMICs). Persistent gaps in knowledge, attitudes, and practices (KAP) undermine public health efforts and perpetuate global inequities in HPV prevention. This dissertation conducts a comprehensive, multi-method investigation of KAP related to HPV and its vaccine among men, mapping global disparities and identifying barriers and facilitators. Methods We adopted a “sandwich” structure, integrating three original studies. First, we conducted a systematic review and meta-analysis of 590 studies to synthesize KAP and HPV vaccine uptake by age, sex, region, and country income level. Second, we conducted a cross sectional survey among Canadian men aged 16 and older to evaluate KAP regarding HPV and its vaccine, and to identify factors influencing KAP in a high-income setting. Third, we conducted a qualitative descriptive study with men, healthcare providers, and policymakers in Bangladesh to gain an in-depth understanding of men's KAP regarding HPV and its vaccine and to identify sociocultural and systemic barriers and facilitators affecting vaccine acceptance in a low- and middle-income context. All studies were guided by the Health Belief Model, providing a unifying theoretical framework for analysis across diverse populations. Results We found substantial global disparities in HPV knowledge and vaccine uptake. Both men and women in low- and middle-income countries exhibited significantly lower knowledge and vaccination coverage compared to those in high-income settings, with younger age groups and males generally having lower KAP levels. We identified key barriers including doubt about HPV vaccine effectiveness, financial constraints, and inadequate access to healthcare services and social, cultural or religious stigma. We observed persistent gaps in HPV-related KAP among men in Canada, primarily due to limited knowledge, insufficient healthcare provider recommendation, and perceived lack of personal risk, even within a well-resourced health system. In contrast, we found a very low knowledge specifically HPV vaccine, widespread misconceptions, sociocultural stigma, lack of research and exclusion of men from vaccination programs to be major barriers to HPV vaccine acceptance and uptake among Bangladeshi men. Conclusions Eliminating global disparities in HPV prevention demands context-specific strategies: in high-income countries like Canada, strengthening healthcare provider engagement and reducing financial barriers are critical to closing persistent gaps in male vaccination; in low and middle-income countries, expanding vaccine access, providing male-focused education, and integrating gender-neutral policies are urgently needed. Implementing these context specific, evidence-based strategies is essential to achieving equitable HPV prevention on a global scale.
Keywords: Human papillomavirus (HPV), HPV vaccine, Knowledge, Attitude, Practice, Global HPV Vaccine uptake, HPV Prevention, Men